2021
DOI: 10.3390/ijms222112044
|View full text |Cite
|
Sign up to set email alerts
|

An Association between Diet and MC4R Genetic Polymorphism, in Relation to Obesity and Metabolic Parameters—A Cross Sectional Population-Based Study

Abstract: The melanocortin-4 receptor (MC4R) gene harbours one of the strongest susceptibility loci for obesity and obesity-related metabolic consequences. We analysed whether dietary factors may attenuate the associations between MC4R genotypes and obesity and metabolic parameters. In 819 participants genotyped for common MC4R polymorphisms (rs17782313, rs12970134, rs633265, and rs135034), the anthropometric measurements, body fat content and distribution (visceral and subcutaneous adipose tissue, VAT and SAT, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Additionally, the impact of T2D differs by population, depending on some variables (e.g., age, race, ethnicity, geography, and socioeconomic status) [11]. Previous studies have found that some environmental factors may regulate the expression of genes and influence susceptibility of T2D, such as gene-diet interaction, in smokers and alcohol drinkers [11][12][13][14][15][16][17]. Few studies have examined the interacitons of other environmental factors with single nucleotide polymorphisms (SNPs) on T2D risk in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the impact of T2D differs by population, depending on some variables (e.g., age, race, ethnicity, geography, and socioeconomic status) [11]. Previous studies have found that some environmental factors may regulate the expression of genes and influence susceptibility of T2D, such as gene-diet interaction, in smokers and alcohol drinkers [11][12][13][14][15][16][17]. Few studies have examined the interacitons of other environmental factors with single nucleotide polymorphisms (SNPs) on T2D risk in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MC4R activation has been shown to result in decreased food intake and increased energy expenditure. Single nucleotide polymorphisms (SNPs) mapped to this gene have been identified as predisposing carriers to obesity and related comorbidities [11,12]. The SNP rs17782313 has been shown multiple times to be associated with obesity [13][14][15][16] and with insulin resistance, dyslipidemia and type 2 diabetes risk [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) allow identifying genetic variants associated with susceptibility to overweight and obesity [7]. In adults, the strongest associations with the risk of obesity were discovered for single-nucleotide polymorphisms (SNPs) in the FTO, MC4R, TMEM18, TNNI3K, SEC16B, GNPDA2, POMC, RPGRIP1L, IRX3, and IRX5 genes [8][9][10][11]. Moreover, it was shown that the genetic susceptibility to obesity is modified in a population-related manner [12][13][14].…”
Section: Introductionmentioning
confidence: 99%